PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP SIKAP ILMIAH PESERTA DIDIK - Widyaningsih Purnama; Arnelia Dwi Yasa; Farida Nur Kumala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Elementary school students generally have a low level of scientific attitude, often preferring to accept information without questioning or analyzing it. This study aims to explore whether using a guided inquiry-based learning approach can improve the scientific attitudes of fourth-grade students when learning about plant body parts at SDN Mergosono 02. The guided inquiry method encourages students to actively engage in discovering knowledge through structured topics, with the teacher acting as a guide. Scientific attitudes are important for developing students' character and critical thinking during learning. The research uses a quasi-experimental design with a Nonequivalent Control Group approach. The sample was selected using saturation sampling, where all students in class IV B, consisting of 21 students, were the experimental group using the guided inquiry model, while class IV A, with 20 students, served as the control group following traditional direct instruction. Data was collected through a scientific attitude questionnaire completed by students and observations made by an observer. The analysis, using an independent sample t-test, showed significant results with a p-value of 0. 001, which is less than 0. 05 at the 5% significance level. The experimental group had an average score of 86. 19, while the control group scored 77. 05. This means the null hypothesis was rejected, and the alternative hypothesis was accepted, showing that the guided inquiry learning model positively impacts students' scientific attitudes when studying plant body parts in fourth grade at SDN Mergosono 02.